2006
DOI: 10.1177/10598405050220040901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patched HOTV Visual Acuity and Photoscreening

Abstract: Early detection of significant vision problems in children is a high priority for pediatricians and school nurses. Routine vision screening is a necessary part of that detection and has traditionally involved acuity charts. However, photoscreening in which "red eye" is elicited to show whether each eye is focusing may outperform routine acuity testing in pediatric offices and schools. This study compares portable acuity testing with photoscreening of preschoolers, kindergarteners, and 1st-graders in 21 element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In one study it was found to be more time-effective and to have a higher positive predictive rate than traditional screening methods. 6 Results with the plusoptiX, obtained by 3 of us (N.S.M., E.L.S., and D.I.S. ), have been published previously.…”
Section: P Ediatric Vision Screeningmentioning
confidence: 95%
“…In one study it was found to be more time-effective and to have a higher positive predictive rate than traditional screening methods. 6 Results with the plusoptiX, obtained by 3 of us (N.S.M., E.L.S., and D.I.S. ), have been published previously.…”
Section: P Ediatric Vision Screeningmentioning
confidence: 95%
“…15,16 Compared with visual acuity testing in younger children, specific objective screening has the benefits of speed, 20 predictive value, 18,19 and cost effectiveness. 17 Specific early objective screening should be followed by sensitive sensory testing to assure that no amblyopic child can pass screening by peeking around an occluder.…”
Section: Discussionmentioning
confidence: 99%
“…The Alaska Blind Child Discovery (ABCD) has attempted to eliminate amblyopia by conducting statewide photoscreening of younger children [ 2 ] and by enhancing patched monocular acuity screening for older children [ 3 ]. Two devices were developed; a quick, portable acuity chart and rolls of patches designed to facilitate affordable, clean, monocular testing.…”
Section: Introductionmentioning
confidence: 99%